Extensive subcutaneous emphysema from scalp to lower limbs in a 44-year old. Issue 12 (30th December 2021) - Sokhal, Balamrit Singh; Prasanna Kumar Menon, Sowmya; Panesar, Harrypal; Rajagopalan, Sriram
Abstract : A 44-year-old man was admitted after being found suspended by his ankles from a bridge for 5 days. The events leading to it was not clearly known initially. On examination, the patient was hypotensive and hypothermic, airway was oedematous and both lower limbs were mottled with dusky feet. Both foot pulses were impalpable, with prolonged capillary refill time and sensation barely present. Doppler signals were not heard in the feet, but groin pulses and popliteal signals were present. On CT, the patient had bilateral pneumothoraxes, extensive subcutaneous emphysema throughout the body from the subcutaneous tissue of the scalp to both lower limbs and pneumomediastinum and pneumoperitoneum. CT angiogram showed opacification up to proximal crural vessels and absence beyond. After multispeciality input and optimisation of his physiology, he underwent bilateral below knee amputations as they were non-salvageable.